Analisis Minat Mahasiswa dalam Berliterasi Sastra melalui Kegiatan Membaca dan Menyimak di Era VUCA - Rina Heryani; Haerul Haerul (Badan Pengembangan dan Pembinaan Bahasa, 2023)
The era of disruption, which is full of uncertain phenomena, has affected the way people think and act today, including in the context of education. This era was later referred to as the era of volatility, uncertainty, complexity, and ambiguity (VUCA). This study aims to analyze the comparative interest of students in literary literacy through reading and listening activities in the VUCA era. The method used in this research is descriptive qualitative method. Research data was collected through the Google Questionnaire instrument which contained statements related to comparisons between students' literary literacy activities through reading and listening activities. The data obtained is then analyzed and interpreted then described. The results of this study indicate that the number of students who are very interested in literature teaching materials in book form, namely 11 people (13.4%), while the number of students who are very interested in literature teaching materials in video form, namely 36 people (43.9%) ). The number of students who were very able to focus on reading literature learning books, namely 20 people (24.4%), while the number of students who were very able to focus on listening to literature learning videos, namely 33 people (40.2%). The number of students who collected information about literature by reading books was 13 people (15.9%), while the number of students who researched information about literature by watching videos was 30 people (36.6%). The number of students who read literature learning books very regularly, namely 7 people (8.5%), while the number of students who very regularly watched literature learning videos, namely 17 people (20.7%). The number of students who strongly agreed to prepare for learning literature by reading books, namely 8 people (9.8%), while the number of students who strongly agreed to prepare for learning literature by watching videos, namely 16 people (19.5%). Therefore, it is necessary to carry out a learning transformation and efforts to increase literary literacy through digitizing learning media. Efforts to improve the quality of literary literacy in the VUCA era cannot only be focused on reading activities, but also utilizing listening activities. AbstrakEra disrupsi yang penuh dengan fenomena ketidakpastian telah mempengaruhi cara berpikir dan bertindak masyarakat saat ini, termasuk dalam konteks pendidikan. Era tersebut kemudian disebut sebagai era volatility, uncertainty, complexity, dan ambiguity (VUCA). Penelitian ini bertujuan untuk menganalisis perbandingan minat mahasiswa dalam berliterasi sastra melalui kegiatan membaca dan menyimak di era VUCA. Metode yang digunakan dalam penelitian adalah metode deskriptif kualitatif. Data penelitian dikumpulkan melalui instrumen google quesioner yang berisi pernyataan-pernyataan terkait perbandingan antara kegiatan berliterasi sastra mahasiswa melalui kegiatan membaca dan menyimak. Data yang diperoleh selanjutnya dianalisis dan diinterpretasi kemudian dideskripsikan. Hasil penelitian ini menunjukkan bahwa jumlah mahasiswa yang sangat tertarik dengan bahan ajar sastra dalam bentuk buku, yaitu 11 orang (13,4%), sedangkan jumlah mahasiswa yang sangat tertarik dengan bahan ajar sastra dalam bentuk video, yaitu 36 orang (43,9%). Jumlah mahasiswa yang sangat mampu memusatkan perhatian dalam membaca buku pembelajaran sastra, yaitu 20 orang (24,4%), sedangkan jumlah mahasiswa yang sangat mampu memusatkan perhatian dalam menyimak video pembelajaran sastra , yaitu 33 orang (40,2%). Jumlah mahasiswa yang menggali informasi tentang sastra dengan membaca buku, yaitu 13 orang (15,9%), sedangkan jumlah mahasiswa yang menggali informasi tentang sastra dengan menyimak video, yaitu 30 orang (36,6%). Jumlah mahasiswa yang sangat rutin membaca buku pembelajaran sastra, yaitu 7 orang (8,5%), sedangkan jumlah mahasiswa yang sangat rutin menyima video pembelajaran sastra, yaitu 17 orang (20,7%). Jumlah mahasiswa yang sangat setuju melakukan persiapan pembelajaran sastra dengan membaca buku, yaitu 8 orang (9,8%), sedangkan jumlah mahasiswa yang sangat setuju melakukan persiapan pembelajaran sastra dengan menyimak video, yaitu 16 orang (19,5%). Oleh karena itu, perlu dilakukan sebuah transformasi pembelajaran dan upaya peningkatan literasi sastra melalui digitalisasi media pembelajaran. Upaya peningkatan kualitas literasi sastra di era VUCA, tidak bisa hanya difokuskan melalui kegiatan membaca, tetapi juga memanfaatkan kegiatan menyimak.